ANALISIS STRATEGI GURU DALAM MEMBENTUK KARAKTER ABAD 21 SISWA PADA PROFIL LULUSAN DI SD NEGERI 23 AMPENAN - Salsabila Putri Ramdani; Asrin; Syarifuddin; Nurul Kemala Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teacher strategies in shaping 21st-century character in students' graduate profiles at SD Negeri 23 Ampenan. This study uses a descriptive qualitative approach. The subjects of the study were fourth and fifth-grade teachers at SD Negeri 23 Ampenan. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis used the Miles and Huberman model. The results showed that teacher strategies in shaping 21st-century character were carried out through project-based learning, collaborative learning through discussion and group work, role models and character value habits, and character assessment through attitude reports. The implementation of these strategies is reflected in the graduate profiles, including the dimensions of faith and devotion to God Almighty, independence, collaboration, and communication. Supporting factors in shaping 21st-century character include the use of digital media, group work habits, the use of attitude reports, and school environmental support. The inhibiting factors faced by teachers include the lack of character habits in the family environment, differences in student character and independence, and the negative influence of gadget use.